Synthesis, Single Crystal, and Physical Properties of Asymmetrical Thiophene/Selenophene‐Fused Twistacenes. Issue 12 (4th September 2015) - Lv, Bo; Shen, Xingxing; Xiao, Jinchong; Duan, Jingdan; Wang, Xuefei; Yi, Yuanping
Abstract: Two asymmetrical twistacenes, PyPT andPyPS, have been synthesized and characterized. Single crystal X‐ray analyses show that both of them have twisted structures with a torsion angle of 26.65° forPyPT and 26.59° forPyPS measured between plane C5‐C23‐C25 and plane C13‐C15‐C26. The thiophene/selenophene‐fused acenes emit blue fluorescence with quantum yields of 0.39 forPyPT and 0.04 forPyPS in organic solvents, whereas the all‐carbon moleculeHBP emits green fluorescence. Meanwhile, PyPT andPyPS show a similar reversible oxide procedure with the onset potentials of 0.73 and 0.72 V, respectively. In addition, PyPT andPyPS can self‐assemble to form nanoparticles in a mixture of THF/H2 O through re‐precipitation method. Abstract : Twist and Shout : Two asymmetrical twistacenesPyPT andPyPS have been synthesized. Single crystal X‐ray analyses showed thatPyPT andPyPS have twisted structures with torsion angles of 26.65° and 26.59°, respectively. Their preliminary optoelectronic properties and self‐assembly behavior were also investigated.